Predictive Analytics as A Service on Moroccan Tax Evasion - Jihal, Houda; Amine Talhaoui, Mohamed; Daif, Abderrahmane; Azzouazi, Mohamed (International Journal of Engineering and Technology, 2018)
Tax evasion is a global problem in governments. It affects society by damaging public accounts and compromising government performance. The government must take a multidisciplinary approach to face this phenomenon. Analytics on big data enables government organizations to improve existing processes and operations and engage in entirely new types of analyses that werenâ€™t possible before. Predictive analytics combines the capabilities of machine learning, statistical analysis and data mining to forecast the future and allows tax authority to prevent tax fraud, reduce the cost of managing taxes and optimize public spending.The purpose of this paper is to predict income from direct Moroccan taxes based on the linear regression model as a first step in the fight of the tax evasion.Â Â